Amended Safety Assessment of Acid Violet 43 as Used in Cosmetics. (October 2021) - Fiume, Monice M; Bergfeld, Wilma F; Belsito, Donald V; Hill, Ronald A; Klaassen, Curtis D; Liebler, Daniel C; Marks, James G; Shank, Ronald C; Slaga, Thomas J; Snyder, Paul W; Gill, Lillian J; Heldreth, Bart
The Expert Panel for Cosmetic Ingredient Safety (Panel) reopened the safety assessment of Acid Violet 43, a cosmetic ingredient that is an anthraquinone dye reported to function in cosmetics as a colorant. This colorant has the same chemical structure as Ext. D&C Violet No. 2, which is a certified colorant; however, Acid Violet 43 is not a certified color and it could have impurities that are not allowed in the certified color. The Panel reviewed relevant new data related to this ingredient and concluded that Acid Violet 43 is safe in the present practices of use and concentration for use in hair dye formulations. This conclusion supersedes the previous conclusion for Acid Violet 43 that included impurity specifications indicated for the certified color.